Ionic Liquid Application in Surfactant Foam Stabilization for Gas Mobility Control - Hanamertani, A.S. (American Chemical Society, 2018)
Foam application in enhanced oil recovery (EOR) processes has been promoted primarily to address the mobility control issue during gas flooding which leads to poor sweep efficiency. Some critical factors such as foam stability and strength in porous media need to be addressed to ensure the effectiveness of foam flooding. In this research, a relatively new additive for foam stabilization composed of ionic liquid (IL) has been introduced. Systematic foam experiments in static condition and porous media were performed to investigate the potential of IL-based additives to enhance surfactant foam stability for gas mobility control. Screening of the mixtures of surfactant and different types of IL was initially conducted based on bulk foam stability measurement at high temperature. Core flooding experiments were then executed to evaluate the foam characteristic using the best formulation in the absence of oil under reservoir conditions. Results from bulk foam experiments indicated that the presence of IL as additive was able to increase foam stability up to a certain extent depending on the type of IL used and its formulation with surfactant. In comparison with the base case, the foam stability increment achieved by the best formulation was 136. The ability of selected IL to lower the surface tension of surfactant solution was found to be in good accordance with its improvement on foam stability. In core flooding experiments, the acceleration of foam generation was noticed in the presence of IL indicated by an immediate increase in mobility reduction factor (MRF) upon early nitrogen injection with 30 increment at the maximum point. A small slug surfactant alternating gas (SAG) injection was able to optimize the performance of the surfactant/IL mixture used in reducing gas mobility by effectively producing stronger foam. This research has provided a strong indication of the capability of IL to perform as additive for foam stabilization, hence improving foam performance in reducing the gas mobility during EOR processes. Â© 2018 American Chemical Society.